KARAKTERISTIK SOSIAL EKONOMI YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI UBI KAYU DI DESA KARANGANYAR BANJARNEGARA - Sarno; Bondan Hary Setiawan (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2014)
Farmer of cassava in Karanganyar village of Banjarnegara have social characteristic different economics with other farmer. Intention of research is to know social characteristic of economics farmer of cassava that is farmer age, other production contribution, amount of family responsibility, wide of farm, and production able to influence level earnings farmer of cassava. Research method the used is method survey approach of case study. Method intake of sampel is Simple Random Sampling. Data analysis is doubled linear regresi with test by parsial (Uji-T) and simultaneously (Uji-F) and also analyse coefficient of determinasi (R2). Result of research indicate that: a). By parsial (Variable Uji-t) old age farmer, amount of family responsibility, and production in the reality do not have an effect on reality to level earnings farmer of cassava, while other production contribution and wide of farm in the reality have an effect on reality, b). Simultaneously (Uji-F) indicate that all social variable of the economics have an effect on manifestly to level earnings farmer of cassava, c). coefficient of determinasi (R2) indicate that level earnings farmer of cassava 97,9% influenced by all variable of social economic, farmer age, while the rest 2,1% influenced by other variable which do not check. Its conclusion that social characteristic of economics influencing level earnings farmer of cassava is farmer age, other production contribution, amount of family responsibility, wide of farm, and production.